Experimental Study Using the Passive Solar Chimney for Evaporative Cooling With PCM and CFM as a Thermal Energy Storage - Murtadha, Talib K.; Salih, Hussien M.; Salman, Ali D. (Al-Khwarizmi Engineering Journal, 2017)
In this work, a test room was built in Baghdad city, with (2*1.5*1.5) m3 in dimensions, while the solar chimneys (SC) were designed with aspect ratio (ar) bigger than 12. Test room was supplied by many solar collectors; vertical single side of air pass with ar equals 25, and tilted 45o double side of air passes with ar equals 50 for each pass, both collectors consist of flat thermal energy storage box collector (TESB) that covered by transparent clear acrylic sheet, third type of collector is array of evacuated tubular collectors with thermosyphon in 45o instelled in the bottom of TESB of vertical SC. The TESB was made from metallic iron sheets as a shell and fuelled by paraffin wax as phase change material (PCM). The PCM supported by copper foam matrix (CFM) to enhance thermal conductivity of wax. When heat is released from TESB to the air, a buoyancy force will be generated in chimney gaps. Then a difference in pressure between inside and outside test room leads to induce the air flow to test room through wet corrugated cellulose pad, where evaporative cooling (EC) occurs. Results of experimental work, that achieved in June, for 12 to24 hour in the test day, refer to effectiveness using EC to decrease the room temperature comparing. The system reduces test room temperature of up to 8.5 9.2 oC in 11:00 am to 3:00 pm and at highest effectiveness of EC, while minimum reduces in temperature of up to 3.5 oC in 8:00pm to 3:00 am. Also, the results showed the affectivity to using the TESB, during the night time for ventilation and EC, with lower effectiveness than from day time. The range of EC effectiveness equals 30.5-37.5 with a natural vent, while The maximum air change per hour (ACH) equals (3.8-6.187), and the maximum mass flow rate is equal to (36.651 kg.hr-1) at experimental evaluation of the system’s discharge coefficient value 0.371.